Inflammatory Markers and Postoperative New-Onset Atrial Fibrillation: Prognostic Predictions of Neutrophil Percent to Albumin Ratio in Patients with CABG - Faruk Serhatlioglu; Yucel Yilmaz; Oguzhan Baran; Halis Yilmaz; Saban Kelesoglu (Diagnostics)
Background/Objectives: Postoperative new-onset atrial fibrillation (AF) (PNOAF) is the most common complication after coronary artery bypass graft (CABG), and its incidence has been reported as up to 50% in studies. In this study, we investigated whether there was a relationship between PNOAF and the neutrophil percentage to albumin ratio (NPAR) levels after on-pump CABG. Methods: A total of 454 patients who underwent CABG were included in the study. NPAR was calculated by dividing the neutrophil count by the albumin value. Results: It was determined that 93 patients developed PNOAF (20.4%). When the patient groups that developed and did not develop PNOAF were compared in terms of laboratory findings, C-reactive protein (CRP) values (4.0 mg/L (2.8–7.9) vs. 2.9 mg/L (1.1–6.7), <0.001), neutrophil/lymphocyte ratio (NLR) (2.2 (1.2–4.2) vs. 1.4 (0.7–3.1), <0.001), platelets-to-lymphocyte ratio (112 (72–177) vs. 92 (69–122), <0.001) and NPAR (2.29 (1.68–3.8) vs. 1.09 (0.79–1.81), <0.001), were found to be statistically significantly higher in the group that developed PNOAF. ROC analysis showed that the cut-off value for NPAR for the development of PNOAF was 1.86 with 78% sensitivity and 72% specificity (area under the ROC curve = 0.778, 95% CI (0.728–0.828), p < 0.001). Conclusions: NPAR, which can be detected by a simple venous blood test, has shown a strong predictive value for PNOAF in patients with CABG.